Konsep Definisi Pendidikan Islam Menurut Al-Hazim - sudarto, sudarto (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2017)
Islamic education is a process of educating man phase out in all aspects of his life to realize the happiness in the world and the hereafter in accordance with methodology of Islam. Anyone who is applying the above process means he has reflected Islamic education. From the above discussion, it can be drawn the conclusion that the al-Hâzimi argued about the existence of the term is included in the Education category, namely al-Ishlâh (repair), an name wa az-ziadah (developing and growing), Nasyaa and Tara'ra ' a ( grow and social interactions), tawalla wa Sâsahu amrahu (lead, mengedalikan and General Affairs), and the Ta'lim (teaching).